PERAN PROFITABILITAS DALAM MEMEDIASI PENGARUH TINGKAT SUKU BUNGA DAN LEVERAGE TERHADAP RETURN SAHAM - Aditya, I Gusti Ngurah Wira; Badjra, Ida Bagus (E-Jurnal Manajemen; Vol 7 No 4 (2018)DO - 10.24843/EJMUNUD.2018.v07.i04.p05, 2018)
The aim of this research is to analyze the influence of interest rate on profitability, the influence of leverage on profitability, the influence of interest rate on stock return, the influence of leverage on stock return, the influence of profitability on stock return, the influence of interest rate on stock return through profitability, the influence of leverage on stock return through profitability. This research is conducted on companies in the building construction sub sector listed in the Indonesian Stock Exchange with a total population of 13 companies and total sample is 7 companies determined using the purposive sampling method. The data analysis technique used is the path analysis and sobel test. Based on analysis results, it was found that interest rate has positive and significant influence on profitability, leverage has positive and significant influence on profitability, interest rate has positive and significant influence on stock return, leverage has positive and significant influence on stock return, profitability has positive but insignificant influence on stock return, profitability is significantly not capable of mediating the influence of interest rate on stock return, and profitability is significantly not capable of mediating the influence of leverage on stock return.